Impedance Spectroscopy Analysis of SnO₂ Nanowires/Carbon Nanotubes Heterojunctions - Quan, Thi Minh Nguyet; Nguyen, Van Duy; Chu, Manh Hung; Nguyen, Van Hieu (Old Journal, 2019)
Impedance spectroscopy is a powerful method for characterizing the electrical properties of semiconductor materials and hybrid structures based on them. In this study, the heterojunctions of SnO₂ nanowires and carbon nanotubes (CNTs) were fabricated by first growing the SnO₂ nanowires on Pt electrodes using a thermal chemical vapour deposition (CVD) method and then dip-coating solution of CNTs. The morphology and characteristics of the SnO₂/CNTs heterojunctions were characterized by a scanning electron microscopy (SEM) and Raman spectroscopy. AC impedance spectroscopy of the SnO₂/CNTs heterojunctions were investigated in the frequency range of 13 MHz to 5 Hz with an oscillating voltage of 10 mV during DC bias of ± 0.4 V at room temperature. The AC equivalent circuit model was developed to gain a deeper understanding of the heterojunctions.